FORMULASI MEDIA PRODUKSI TUBUH BUAH JAMUR TIRAM PUTIH (Pleurotus ostreatus (Jacq.) P. Kumm), BERBAHAN DASAR LIMBAH TANDAN KOSONG KELAPA SAWIT DAN SERBUK GERGAJI - Umrah, Umrah; Yuniati, Eny; Azzahra, Andini Shafa Arezy Azzahra (Biocelebes, 2025)
This research aims to determine the growth and production as well as the optimal dosage for white oyster mushroom fruiting bodies on a basic substrate of oil palm empty fruit bunch and sawdust. The study was designed using a completely randomized design (CRD) with seven treatments and three replications. The treatment media consisted of oil palm empty fruit bunch (LSTKKS), sawdust (SG), rice bran (DP), and CaCO3 lime. The treatments were as follows: P1 (LSTKKS 1000 g + Lime 20 g), P2 (LSTKKS 800 g + SG 200 g + DP 100 g + Lime 20 g), P3 (LSTKKS 600 g + SG 400 g + DP 100 g + Lime 20 g), P4 (LSTKKS 500 g + SG 500 g + DP 100 g + Lime 20 g), P5 (LSTKKS 400 g + SG 600 g + DP 100 g + Lime 20 g), P6 (LSTKKS 200 g + SG 800 g + DP 100 g + Lime 20 g), P7 (SG 1000 g + DP 100 g + Lime 20 g). The parameters used in the study included mycelium growth on the substrate, incubation period until pinhead formation, number of pinheads, incubation period until fruiting body formation, number of fruiting bodies, fruiting body morphology, fresh weight of fruiting bodies, and dry weight of fruiting bodies. The results showed that mushrooms could grow on all treatment media, but the best growth and production occurred in treatments P4 with a dosage of 500 g oil palm empty fruit bunch + 500 g sawdust + 100 g rice bran + 20 g lime and treatment P5 with a dosage of 400 g oil palm empty fruit bunch + 600 g sawdust + 100 g rice bran + 20 g lime